WAKAF TUNAI SEBAGAI ALTERNATIF PEMBERDAYAAN EKONOMI UMMAT ISLAM DI INDONESIA - Zaidah, Yusna (At-Taradhi, 2012)
A disproportional understanding on wakaf assets, emphasising their immortality, cause people to give only non-moving things, mainly lands, as wakaf, while historically, Muslims also donated money or cash wakaf. This must become a common concern. Cash wakaf can be employed as an instrument to boost the economy of Muslim community through investments. It also supplements other philanthropic funds. Moreover, cash wakaf will provide a huge support to make non-moving wakaf assets more productive. Unused wakaf lands can be transformed into cash machines, using wakaf money, for example by making them cultivation areas, or to build factories, offices or a business center. By doing so, we do not need to depend on loans from foreign countries to alleviate poverty.Â